Lysophospholipids and Their G-Coupled Protein Signaling in Alzheimer’s Disease: From Physiological Performance to Pathological Impairment - Yining Hao; Min Guo; Yiwei Feng; Qiang Dong; Mei Cui (Frontiers in Molecular Neuroscience, 2020)
Lysophospholipids (LPLs) are bioactive signaling lipids that are generated from phospholipase-mediated hydrolyzation of membrane phospholipids (PLs) and sphingolipids (SLs). Lysophosphatidic acid (LPA) and sphingosine-1-phosphate (S1P) are two of the best-characterized LPLs which mediate a variety of cellular physiological responses via specific G-protein coupled receptor (GPCR) mediated signaling pathways. Considerable evidence now demonstrates the crucial role of LPA and S1P in neurodegenerative diseases, especially in Alzheimer’s disease (AD). Dysfunction of LPA and S1P metabolism can lead to aberrant accumulation of amyloid-β (Aβ) peptides, the formation of neurofibrillary tangles (NFTs), neuroinflammation and ultimately neuronal death. Summarizing LPA and S1P signaling profile may aid in profound health and pathological processes. In the current review, we will introduce the metabolism as well as the physiological roles of LPA and S1P in maintaining the normal functions of the nervous system. Given these pivotal functions, we will further discuss the role of dysregulation of LPA and S1P in promoting AD pathogenesis.